2016
DOI: 10.1007/s12520-016-0447-4
|View full text |Cite
|
Sign up to set email alerts
|

Glassmaking using natron from el-Barnugi (Egypt); Pliny and the Roman glass industry

Abstract: Pliny the Elder describes the discovery of a process for making natron glass, which was widely used for much of the first millennium BC and AD. His account of glassmaking with natron has since been corroborated by analyses of archaeological glass and the discovery of large-scale glass production sites where natron glass was made and then exported. Analyses of Egyptian natron have shown it to be a complex mixture of different sodium compounds, and previous experiments to make glass with Egyptian natron have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(16 citation statements)
references
References 20 publications
(25 reference statements)
0
16
0
Order By: Relevance
“…These lead glasses have exceptionally high chlorine values (1.7%–2.5%), negatively correlated with calcium. It has been shown that the chlorine content decreases with increasing temperature and calcium oxide content [ 66 ]. This could explain the high chlorine level, because the lime concentrations are very low and the melting temperature of glass with high lead content (PbO > 40%) is drastically reduced.…”
Section: Resultsmentioning
confidence: 99%
“…These lead glasses have exceptionally high chlorine values (1.7%–2.5%), negatively correlated with calcium. It has been shown that the chlorine content decreases with increasing temperature and calcium oxide content [ 66 ]. This could explain the high chlorine level, because the lime concentrations are very low and the melting temperature of glass with high lead content (PbO > 40%) is drastically reduced.…”
Section: Resultsmentioning
confidence: 99%
“…Jackson, Paynter, Nenna, and Degryse () have recently suggested that a negative correlation between CaO and Cl among Roman glass groups and experimental glass synthesized using Egyptian natron is a signature of primary glass production. The lack of a similar correlation among the Byzantine glasses of Jerash ( R 2 = 0.2) does not exclude this possibility, but does suggest that additional factors affect Cl and Ca in Levantine glasses.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the strong negative K-Cl correlation (R 2 = 0.63) compared to other sites in the region (Umm el-Jimal at 0.25 and Petra at 0.24), in addition to even stronger positive K-P correlation (R 2 = 0.88; Figure 12), suggests that glass recycling was more intensive at Jerash. Jackson, Paynter, Nenna, and Degryse (2016) have recently suggested that a negative correlation between CaO and Cl among Roman glass groups and experimental glass synthesized using Egyptian natron is a signature of primary glass production. The lack of a similar cor- (Carroll, 2005;Metrich & Rutherford, 1992;Veksler et al, 2012).…”
Section: Influence From Fuel and Furnaces During Recycling In Jerashmentioning
confidence: 99%
“…The pXRF analyses also reveal the presence of other chemical elements, such as aluminium, titanium, iron, or antimony (Table 2). As natron contains very low amounts of impurities, minor and trace elements certainly originate from sand (Ti, Al, and Fe), decolouring (Mn and Sb) or colouring (Co, Cu, Fe, and Sb) agents (see below), and/or sometimes from recycling processes (Sb, Sn, Pb, Ni, and Cu) [19,33]. Sodalime glasses with natron were exclusively used until the beginning of the Middle Age, before being gradually replaced by wood and plant ashes to almost disappear during the 13th century [20,25,27,28].…”
Section: Composition and Dating Of Glass Beadsmentioning
confidence: 99%